From start-up to global success : the Zensār story - Natarajan, Ganesh; Kalive, Prameela (SAGE Publications, 2016)
The story of Zensar Technologies" presents the evolution, growth and successful model of a software firm! Unvail the 'secret sauce' behind Zensar's Success.